Time lag effects of IT investment on firm performance : evidence form Indonesia - Winarno, Wahyu Agus; Tjahjadi, Bambang; Irwanto, Andry (Penerbit Universiti Kebangsaan Malaysia, 2021)
The objective of this study is to investigate whether there is a lag effect of IT investment on the financial performance of the firm, both individual and industry-adjusted firm performance. Using a dynamic panel approach of Generalized Method of Moments, we sourced data from 396 firms from multiple companies listed on the Indonesia Stock Exchange over 2013-2017. The results indicate that IT investment improves the firm financial performance after the first year of investment. IT investment in the current period does not affect its current financial performance because it requires a time lag for the firm to realize its benefits due to the organizational learning process, structural effects, and complementary effects. However, we found an immediate impact of IT investment on firm performance when performance is measured by market performance. Information on IT investment is good news for investors hence the stock price that reflects the future performance of the firms.